Foreign Ownership and Strike Activity in Canada - Cousineau, J.-M.; Lacroix, R.; Vachon, D. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
This microeconomic study of strike activity adds to an already tested empirical strike model, variables that are related to foreign-owned firms in Canada. AU results converge to the same and unique conclusion: foreign-owned firms in Canada show a lower strike propensity, everything else being constant. Such a result suggests that multinational firms may well develop bargaining "protocoles" that overcompensate problems of credibility and information expected to be associated with foreign-owned property.